The genus Attalea (Arecaceae) of Bolivia: regional ecologic system affinities - Mónica Moraes R.; Freddy S. Zenteno-Ruiz (Revista Peruana de Biología, 2017)
The documentation of the Neotropical species of the Arecaceae family, based on the recent contributions to its taxonomy and its relationship with natural landscapes, updates the spatial patterns to which they adapt in their range of distribution. In this case 121 records of specimens of the 11 species of the genus Attalea of Bolivia and their relationship with 30 ecological systems that approximate their scope of distribution at regional level are released. To this end, the geographical coordinates were systematized, verified and corrected. Localities of all the specimens collected from the genus Attalea in order to compare them with ecological systems, using the ArgGis tools. We then elaborate a dendrogram (species vs. ecological systems) using the minimum distance method in the R program. The analysis of the relation of the species with the ecological systems highlights a species that does not compose to the southwest amazon: A. eichleri and that is native to ecological systems of the Cerrado. Among the SW Amazonian Attalea species, A. blepharopus (endemic to Bolivia) is isolated from the others and the rest subgroup species according to their presence in forests and savannas, in addition to the subandean and alluvial, as it is for A. princeps, which is found in 17 systems (57%). Eight species of Attalea are common with Peru and 10 with Brazil. It is important to relate the hierarchical grouping of the Attalea species with ecological systems in function of landscape dynamics to document their space patterns and also for their conservation.